Study Of Indirect Fibromarkers inIdentifying theDegree ofLiver Fibrosis During Antiviral Therapy Of Patients With Hepatitis HCV Etiology - Bayjanov A.K; Nasirova Х.P; Khikmatullaeva A.S; Abdukadirova M.A; Yarmukhamedova N.A; Raximova V.Sh; Brigida K.S.; Ibadullaeva N.S; Mirrakhimova N.M; Каn N; Matyakubova Feruza Egamovna (Zien Journals, 2024)
This  work  examined  the  diagnostic  role  of  biomarkers -APRI, alpha-fetoprotein–AFP  and gammaglutamine transpeptidase–GGTP before and after antiviral therapy in patients with different degrees of liver fibrosis. At the same time, there was a decrease in these indicators after treatment, which indicates a reverse development of liver fibrosis after specific therapy.During therapy, a significant decrease in APRI from 0.67 to 0.33 (p<0.05), AFP from 4.82 to 1.77 (p<0.01) and GGTP from 42.4 to 26.8 was established (p<0.05).  Thus,  APRI,  AFP  and  GGTP  indicators  can  be  used  as  dynamic  markers  for  assessing  the antifibroticeffect of etiotropic therapy for hepatitis C
Keywords: hepatitis C virus; fibrosis; APRI